How to solve this 336+x/5=85

Answers

Answer 1

Answer:

x = -1255

Step-by-step explanation:

336+x/5=85

Subtract 336 from each side

336-336 +x/5=85-336

x/5 =-251

Multiply each side by 5

x/5 * 5 = -251 *5

x = -1255


Related Questions

Oscar gained x pounds within the last year. he weighed 96 pounds last year. which expressions correctly describes his current weight?
a. 96 - x
b. 96 + x
c. 96x
d. 96/x

Answers

Answer:

b

becasue to find his current weight you would use what you know and the amount of lbs he added (represented as x)

96 + x

Step-by-step explanation:

B !!!!!!!!!!!!!!!!!!!!!!!!

Sally is near the end of a three year lease on a car with an original MSRP of $38,000. Her leasing company claims that the car is now worth only $28,500. Which percentage represents the residual value of Sally’s leased car?
a.
25%
b.
33%
c.
67%
d.
75%

Answers

Answer:

Option D is correct.

Step-by-step explanation:

Original Price of car = $38,000

Current Price of car = $28,500

The residual value of Sally's leased car = x = ?

Residual value * Original Price = Current Price

x * 38,000 = 28,500

x = 28,500/38,000

x = 0.75

Since we need to find percentage

Multiply the residual value with 100 i.e,

0.75 * 100 = 75%

Option D is correct.

Option D is correct from how the three tear lease on a car with an original MSRP of $38,00

if f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)

Answers

Answer:

(f-g)(x) = x-3

Step-by-step explanation:

Given

f(x) = 3x-2

and

g(x) = 2x+1

We have to find (f-g)(x)

So,

(f-g)(x) = f(x)-g(x)

= 3x-2 - (2x+1)

= 3x-2-2x-1

=x-3

Hence,

(f-g)(x) = x-3

Answer:

( f - g ) ( x ) = x - 3

Step-by-step explanation:

We are to find [tex] ( f - g ) ( x ) [/tex] given that [tex] f ( x ) = 3 x - 2 [/tex] and [tex] g ( x ) = 2 x + 1 [/tex].

So basically we have to subtract the function g from function f.

[tex] ( f - g ) ( x ) = f(x) - g(x) [/tex]

Substituting the given functions in the above equation to get:

[tex] ( f - g ) ( x ) = (3x - 2) - (2 x + 1 ) [/tex]

[tex] ( f - g ) ( x ) = 3x - 2 - 2 x - 1  [/tex]

[tex] ( f - g ) ( x ) = 3x - 2 x - 2 - 1  [/tex]

[tex] ( f - g ) ( x ) = x - 3 [/tex]

if f(x)=(x+3)³+4
let g(x)=f(x+1)-2
find when g(x)=12

Answers

Answer:

[tex]x=\sqrt[3]{10}-2[/tex]

Step-by-step explanation:

The composite function (f(x+1)) is moved in the x-axis by -1, you know this by solving x+1=0.

The equivalent expresion for f(x+1) is

[tex]f(x+1)= (x-1+3)^{3}+4[/tex]

[tex]f(x+1)=(x+2)^{3}+ 4[/tex]

Eval the above expression in g(x)

[tex]g(x)=(x+2)^{3}+4-2[/tex]

We must find x that gives g(x)=12

The equation is the following

[tex]12=(x+2)^{3}+2[/tex]

Grouping terms>

[tex](x+2)^{3} =10[/tex]

To solve for x, must apply cubic root in both sides of equation:

[tex]\sqrt[3]{(x+2)^{3} } =\sqrt[3]{10}[/tex]

it then turns in the following>

[tex]x+2=\sqrt[3]{10}\\[/tex]

Giving the stated answer

Enter a recursive rule for the geometric sequence.

2,−6,18,−54,...

Answers

Answer:

[tex]a_n=-3a_{n-1}[/tex] where [tex]a_1=2[/tex]

Step-by-step explanation:

Recursive means you want to define a sequence in terms of other terms of your sequence.

The common ratio is what term divided by previous term equals.

The common ratio here is -6/2=18/-6=-54/18=-3.

Or in terms of the nth and previous term we could say:

[tex]\frac{a_n}{a_{n-1}}=r[/tex]

where r is -3

[tex]\frac{a_n}{a_{n-1}}=-3[/tex]

Multiply both sides by the a_(n-1).

[tex]a_n=-3a_{n-1}[/tex] where [tex]a_1=2[/tex]

Answer:

see explanation

Step-by-step explanation:

A recursive rule allows us to obtain any term in the sequence from the previous term.

These are the terms of a geometric sequence with common ratio r

r = - 6 ÷ 2 = 18 ÷ - 6 = - 54 ÷ 18 = - 3

Thus to obtain a term in the sequence multiply the previous term by - 3

[tex]a_{n+1}[/tex] = - 3 [tex]a_{n}[/tex] with a₁ = 2

05.07) The net of a pyramid is shown below: The net of a square based pyramid, with bases labeled 7 inches and the height of the triangle labeled 14 inches. The surface area of the solid is ____ square inches. Numerical Answers Expected!

Answers

Answer: 245 [tex]in^{2}[/tex]

Step-by-step explanation:

You can find the Surface Area of a figure by adding up the areas of each shape.

First you have to find the area of the base.

7×7 = 49

Then you can find the area of the 4 triangles that complete the pyramid.

Formula for area of a triangle: [tex]\frac{1}{2} bh[/tex] (one half of base times height)

[tex]\frac{1}{2} (14*7) = x\\\frac{1}{2} 98 = x\\x = 49[/tex]

Since all the triangles are the same, you only have to calculate that once.

Now you just add everything together, and that's your surface area.

[tex]49+49+49+49+49= 245[/tex]

Please mark brainly if it helped you out!~

Answer:  245

Step-by-step explanation:

first you have to 7 for the square which = 14

then after that you do 1/2 b x h = 1/2  7 x 14= 3.5 x 14= 49 but then you have 4 triangles so 49 x 4=196.     Then  49 + 196= 245  

what are the domain and range of the absolute value parent function

Answers

Answer:

C. The domain is all real numbers, and the range is non-negative real numbers( [tex]y\ge0[/tex])

Step-by-step explanation:

The absolute value parent function is [tex]y=|x|[/tex]

The domain of a function refers to all values of x for which the function is defined.

The parent absolute value function is defined for all values of x.

Therefore the domain is all real numbers.

The range refers to the y-values for which x is defined.

The parent has a v-shape and its vertex is at the origin.

Therefore the least y-value is 0 and there is no maximum y-value.

The range is [tex]y\ge0[/tex]

See attachment.

which of the following is a factor of 6x^3 + 6?
a) x - 1
b) x + 1
c) x² - 2x + 1
d) x² + x + 1​

Answers

Answer:

B

Step-by-step explanation:

Given

6x³ + 6 ← factor out 6 from each term

= 6(x³ + 1)

x³ + 1 is a sum of cubes and factors as

x³ + 1 = (x + 1)(x² - x + 1)

Hence

6x³ + 6 = 6(x + 1)(x² - x + 1)

With factor (x + 1) → B

Answer:

b) x + 1

Step-by-step explanation:

you can either

1) take (6x³ + 6) and divide by all the choices to see which one gives you a factor. You will realize that if you divide this by option b, you will be able to factorize the equation as follows:

(6x³ + 6) = 6(x+1)(x²−x+1)

Hence option b is a factor

or

2) (my preferred method), utilize the properties of functions and roots.

Let function f(x) = 6x³ + 6

any value of a which gives f(a) = 0 is a root , i.e (x-a) is a factor.

In this case, lets consider option b

let x + 1 = 0 -------> or x = -1

substitute this into the function f(x)

f(-1) = 6 (-1)³ + 6

f(-1) = -6 + 6 = 0

hence x = -1 is a root , or (x+1) is a factor.

as a sanity check, lets try choice a) x -1

let x - 1 = 0 -------> or x = +1

substitute this into the function f(x)

f(1) = 6 (1)³ + 6

f(1) = 6 + 6 = 12 ≠0

hence x = 1 is NOT a root , or (x-1) is NOT a factor.

You can do the same for c and d and find that they too are NOT factors.

what is the midpoint of the verticle line segment graphed below?​

Answers

Answer:

C (2, -5/2)

Step-by-step explanation:

To find the midpoint of two points

mid = (x1+x2)/2, (y1+y2)/2

       = (2+2)/2, (4+-9)/2

       = 4/2, -5/2

       =2,-5/2

In the triangle, BC is the length of the mid-segment. Find the length of DE.​

Answers

11.2cm
The mid segment is exactly 1/2 of the length of DE. Since BC is 5.6cm you just multiply that by two to find your answer.


A​ single, six-sided die is rolled. Find the probability of rolling an even
number or a number less than 3


Answers

Answer:

5/6 (if including 3)       4/6 (not including 3)

Step-by-step explanation:

1 and 2 are less than 3

4 and 6 are even

that leaves 5 and 3.

so 4 of the numbers are even or less than 3

Probability of rolling even number or number less than 3 is 2/3.

What is probability?

Probability is defined by the possibility of the event to happen which is ratio of no. of favorable outcomes and the total no. of outcomes.

Probability of event = P(E) = No. of favorable outcomes/Total No. of outcomes

Here given that the dice is fair and six-sided is rolled.

Total no. of outcomes by rolling the dice=6 i.e. {1,2,3,4,5,6}

No. of favorable outcomes of getting even no. =3 i.e. {2,4,6)

Probability of rolling an even no.=P(even)= No. of favorable outcomes/Total No. of outcomes = 3/6

No. of favorable outcomes of getting no. less than 3 =2 i.e. {1,2}

Probability of rolling no. less than 3=P(<3) =No. of favorable outcomes/Total No. of outcomes = 2/6

No. of favorable outcomes of getting even no and number less than 3 =1 i.e. {2}

Probability of rolling an even no. and no. less than 3 =P(even and <3) = P(even ∩ <3)= No. of favorable outcomes/Total No. of outcomes = 1/6

As we know P(A∪B)=P(A)+P(B)-P(A∩B)

Probability of rolling an even no.or no. less than 3 = P(even or <3) = P(even ∪ <3)= P(even)+P(<3)-P(even ∩ <3)

=(3/6)+(2/6)-(1/6)

=4/6

=2/3

Therefore probability of rolling even number or number less than 3 is 2/3.

Learn more about probability

here: https://brainly.com/question/14192140

#SPJ2

What is the greatest common factor of the polynomial 40x^7+135x^4+5x^4

Answers

5x^4

Step-by-step explanation:

simply we take 5x^4 bec. it can be divided by 40 and 135

What is the measure of angle E, in degrees?

Answers

The answer is 84 degrees because d and f both are 48 degrees so that adds up to 96. So that means you add 84 plus 96 which is 180 so the answer is 84 degrees.

Answer. The answer is 84

mk
---, for m = 6 and k = 2
m+k

Answers

Don’t know what the question is asking
mk=6*2=12
m+k=6+2=8

So you're asking to evaluate this equation?

mk/m+k for m = 6 and k = 2

Inverse of f(x)=3x-4

Answers

Answer:

[tex]\large\boxed{f^{-1}(x)=\dfrac{x+4}{3}=\dfrac{1}{3}x+\dfrac{4}{3}}[/tex]

Step-by-step explanation:

[tex]f(x)=3x-4\to y=3x-4\\\\\text{exchange x to y and vice versa}\\\\x=3y-4\\\\\text{solve for y}\\\\3y-4=x\qquad\text{add 4 to both sides}\\\\3y=x+4\qquad\text{divide both sides by 3}\\\\y=\dfrac{x+4}{3}[/tex]

Which of the following best describes the locust of points equidistant from a given directrix and focus?
A. Parabola
B. Circle
C. Ellipse
D. Hyperbola

Answers

Answer:

A. Parabola

Step-by-step explanation:

Parabola best describes the locust of points equidistant from a given directrix and focus.

Parabola is the curve that best describes the locus of points equidistant from a given directrix and focus. This can be obtained by understanding what a parabola is.

What is a parabola?Parabola is a locus of points equidistant from a given fixed point and fixed line.The fixed point is focus and the fixed line is directrix.Standard equation of a parabola:

The equation is y² = 4ax, when directrix is parallel to the y-axis, a is distance from origin to focus.

Hence parabola is the curve that best describes the locus of points equidistant from a given directrix and focus.

Learn more about parabola here:

brainly.com/question/4074088

#SPJ2

Type the correct answer in each box.

The value of x is °, and the value of y is
°.

Answers

Answer:

x = 60°, y = 50°

Step-by-step explanation:

We know: the angles measures in a triangle add up to 180°.

(look at the picture)

z + 50 + 60 = 180

z + 110 = 180    subtract 110 from both sides

z = 70°

x + 50 + 70 = 180

x + 120 = 180         subtract 120 from both sides

x = 60°

Angles x, y and z are on one side of a straight line. Therefore they add to 180°.

x + y + z = 180

60 + y + 70 = 180

y + 130 = 180         subtract 130 from both sides

y = 50°

Answer:

x = 60°, y = 50°

Step-by-step explanation:

We know: the angles measures in a triangle add up to 180°.

z + 50 + 60 = 180

z + 110 = 180    subtract 110 from both sides

z = 70°

x + 50 + 70 = 180

x + 120 = 180         subtract 120 from both sides

x = 60°

Angles x, y and z are on one side of a straight line. Therefore they add to 180°.

x + y + z = 180

60 + y + 70 = 180

y + 130 = 180         subtract 130 from both sides

y = 50°

Choose the correct product of (6x + 2)2.

Answers

Answer:

36x² + 24x + 4

Step-by-step explanation:

Given

(6x + 2)² = (6x + 2)(6x + 2)

Each term in the second factor is multiplied by each term in the first factor, that is

6x(6x + 2) + 2(6x + 2) ← distribute both parenthesis

= 36x² + 12x + 12x + 4 ← collect like terms

= 36x² + 24x + 4

Complete the square to solve the equation below x^2 + 10x - 13 = 17

Answers

Answer:

x =  -12.42    or  x = 2.42

Step-by-step explanation:

x^2 + 10x - 13 = 17

To solve this using the completing the square method, we will follow the  steps below;

First, we will add 13 to both side of the equation, we want only the x variable to be on the left-hand side of the equation

x^2 + 10x - 13 + 13 = 17 + 13

x^2 + 10x  = 30

The next step is to add both-side of the equation  by square of half of the coefficient of x (that is ; half of 10 is 5, then we will add 5²  to both-side of the equation)

x^2 + 10x + 5²  = 30 + 5²

Then we can now factorize the left-hand side of the equation and at the same time simplify the right-hand side of the equation

(x + 5)²   =   30 + 25

(x + 5)²   = 55

We will then take the square root of both-side of the equation

√(x + 5)²   = ±√55

x + 5  =  ±√55

To get the value of x, we will subtract 5 from both-side of the equation

 x + 5 - 5   =  ±√55 - 5

x =  ±√55  -  5

Either x = + √55 -5  = 7.42 -5 = 2.42

OR

x = -√55 - 5   = -7.42 - 5 = -12.42

Therefore either x =  -12.42    or  x = 2.42

 x =  -12.42    or   2.42


The correct answer will be: x=-5+√55 ; x=-5-√55

Hope this helps!!

Osvoldo has a goal of getting at least 30%, percent of his grams of carbohydrates each day from whole grains. Today, he ate 220 grams of carbohydrates, and 55grams were from whole grains.

Did Osvoldo meet his goal? How many grams of whole grain did he eat?

Answers

Answer:

Osvoldo does not meet his goal

He had to have eaten at least 66 grams of whole grains to meet his goal.

Step-by-step explanation:

step 1

Find out the 30% of the grams of carbohydrates that Osvoldo ate today

Remember that

30%=30/100=0.30

so

0.30(220)=66 grams

step 2

Compare the 30% of the grams of carbohydrates that Osvoldo ate today with the 55 grams of whole grains

we know that

To Osvoldo meet his goal the 55 grams of whole grain must be greater than or equal to the 30% of the grams of carbohydrates that Osvoldo ate today

55 < 66

therefore

Osvoldo does not meet his goal

He had to have eaten at least 66 grams of whole grains to meet his goal.

Find the value of -36+(-9)+14+(-31)-(-66)

Answers

Answer:

4

Step-by-step explanation:

-36-9+14-31+66

=4

Since + - = - and - - = +

❤️❤️☺️Hello MATHS Experts☺️❤️❤️, Solve This Problem Please​

Answers

Answer:

x = 70°y = 55°z = 55°

Step-by-step explanation:

Look at the picture.

We know: the sum of the angles measure in the triangle is 180°. Therefore we have the equation:

[tex]35^o+35^o+\alpha=180^o[/tex]

Solve it:

[tex]70^o+\alpha=180^o\qquad\text{subtract}\ 70^o\ \text{from both sides}\\\\\alpha=110^o[/tex]

Angle α and β = x are the supplementary angles. Supplementary angles add up to 180°. Therefore:

[tex]\alpha+\beta=180^o[/tex]

[tex]110^o+\beta=180^o\qquad\text{subtract}\ 110^o\ \text{from both sides}\\\\\beta=70^o[/tex]

[tex]\beta+\gamma+\gamma=180^o[/tex]

[tex]70^o+2\gamma=180^o\qquad\text{subtract}\ 70^o\ \text{from both sides}\\\\2\gamma=110^o\qquad\text{divide both sides by 2}\\\\\gamma=55^o[/tex]

What is the solution​

Answers

Answer:

y  ≥ 14.

Step-by-step explanation:

y - 27 ≥ -13 Add 27 to both sides:

y  ≥ 14 (answer).

For this case we must find the solution of the following inequality:

[tex]y-27 \geq-13[/tex]

We must add 27 to both sides of the inequality:

[tex]y \geq-13 + 27[/tex]

We know that different signs are subtracted and the sign of the major is placed.[tex]y \geq14[/tex]

So, the solution is [tex]y \geq14[/tex]

Answer:

Option C

please answer this.
Also if you can, please answer my other question its very simmilar

Answers

For this case we have that a percentage equivalent to[tex]\frac {1} {8}[/tex]is given by:

[tex]x = \frac {1} {8} * 100 =[/tex] 12.5%

Then, according to the steps, it is observed that Harriet made an incorrect division, deboa multiply. So, the second step is the wrong one.

Answer:

Option B

Lela purchased three mechanical pencils and a notebook that cost five dollars per purchase totaled $11 how much was each pencil use P to represent the cost of each pencil

Answers

Answer: 3p+5=11

Step-by-step explanation:

3p+5=11

-5 -5

3p=6

3p/3=6/3

P=2

$2

The cost of each pencil is $2.

What is a word problem?

A word problem is a verbal description of a problem situation. It consists of few sentences describing a 'real-life' scenario where a problem needs to be solved by way of a mathematical calculation.

For the given situation,

Number of pencils = 3

Number of notebook = 1

Cost of a notebook = $5

Total cost = $11

Let number of pencil be p.

Lela purchased three mechanical pencils and a notebook is

⇒ [tex]3p+5=11[/tex]

⇒ [tex]3p=11-5[/tex]

⇒ [tex]3p=6[/tex]

⇒ [tex]p=\frac{6}{3}[/tex]

⇒ [tex]p=2[/tex]

Hence we can conclude that the cost of each pencil is $2.

Learn more about word problems here

brainly.com/question/20594903

#SPJ2

(1/x)+(1/x-y)
Please solve this question. I will mark you brainliest.

Answers

Answer:

[tex]\frac{2x-y}{x(x-y)}[/tex]

Step-by-step explanation:

To express as a single fraction

multiply numerator/denominator of [tex]\frac{1}{x}[/tex] by (x - y) and

multiply numerator/ denominator of [tex]\frac{1}{x=y}[/tex] by x

= [tex]\frac{x-y}{x(x-y)}[/tex] + [tex]\frac{x}{x(x-y)}[/tex]

Add the numerators leaving the denominator

= [tex]\frac{2x-y}{x(x-y)}[/tex]

You deposit $5000 in an account earning 8% interest compounded monthly. How much will you have in the account in 15 years?

Answers

[tex]\bf ~~~~~~ \textit{Compound Interest Earned Amount} \\\\ A=P\left(1+\frac{r}{n}\right)^{nt} \quad \begin{cases} A=\textit{accumulated amount}\\ P=\textit{original amount deposited}\dotfill &\$5000\\ r=rate\to 8\%\to \frac{8}{100}\dotfill &0.08\\ n= \begin{array}{llll} \textit{times it compounds per year}\\ \textit{monthly, thus twelve} \end{array}\dotfill &12\\ t=years\dotfill &15 \end{cases}[/tex]

[tex]\bf A=5000\left(1+\frac{0.08}{12}\right)^{12\cdot 15}\implies A=5000(1.00\overline{66})^{180}\implies A\approx 16534.61[/tex]

Solve this radical equation (square root of x+11)-x=-1

Answers

[tex]\bf \sqrt{x+11}-x=-1\implies \sqrt{x+11}=x-1\implies \stackrel{\textit{squaring both sides}}{(\sqrt{x+11})^2=(x-1)^2} \\\\\\ x+11=\stackrel{\mathbb{F~O~I~L}}{x^2-2x+1}\implies 11=x^2-3x+1\implies 0=x^2-3x-10 \\\\\\ 0=(x-5)(x+2)\implies x= \begin{cases} 5\\ -2 \end{cases}[/tex]

Gives x = -5 or x = 2.

Learn how to solve radical equations step by step by isolating terms and squaring, resulting in solutions to the given equation.

To solve the equation (square root of x+11)-x=-1, follow these steps:

Isolate the square root term: square root of x+11=-1+xSquare both sides to eliminate the square root: x+11 = x^2+2x+1Rearrange the equation and solve the quadratic: x^2+x-10=0, which gives x = -5 or x = 2

What is the solution to the equation x over 3 + x over 6 = 7 over 2

Answers

Answer:

x=7

Step-by-step explanation:

The given equation is:

[tex]\frac{x}{3}+\frac{x}{6} = \frac{7}{2}[/tex]

Multiplying both sides by LCM of 3 and 6

So,

[tex]\frac{x}{3}*6+\frac{x}{6}*6 = \frac{7}{2}*6\\2x+x=7*3\\3x=21\\\frac{3x}{3} =\frac{2}{3}\\ x=7[/tex]

Hence, the solution of the equation is x=7 ..

Answer: x = 7

Step-by-step explanation:

(x/3)+(x/6)=7/2

add variables

(2x+x)/6=7/2

combine like terms

3x/6=7/2

simplify

x/2=7/2

multiply denominators by 2

x=7

Ir x represents a postive
number, select all expressions
whose valve is greater than X.
A.(1 - 1-4)x
B.(1 + 1/4)x
C. 7/8x
D. 9/8x

Answers

Answer:

I think it may be B, but double check

Answer:

B and D

Step-by-step explanation:

Considering the multiple choices and let us assume that x = 2,

Option A would be equal to [tex]\frac{3}{4}x[/tex],

so if x = 2, then;

        [tex]\frac{3}{4}x[/tex] = 1.5 (which is less than x)

Option B would give [tex]\frac{5}{4} x[/tex],

so if x = 2, then;

       [tex]\frac{5}{4} x[/tex] = 2.5 ( which is greater than x)

From option C,

      [tex]\frac{7}{8} x[/tex] = 1.75 (which is less than x)

From option D,

     [tex]\frac{9}{8} x[/tex] = 2.25 ( which is greater than x)

So, options B and D are expressions whose values are greater than x.

Other Questions
Select the sources of tax revenue for federal, state, and local governments. Select all that apply.personal incomesalespayrolleducation How to write a Cprogram to print all the prime numbers between 1and n where n is the value supplied by the users. Identify the "c" value of the following quadratic equation given below.-8 = 2(x + 9)^2 The 1H NMR signal for bromoform (CHBr3) appears at 2065 Hz when recorded on a 300MHz NMR spectrometer. If the spectrum was recorded on a 500MHz instrument, what would be the chemical shift of the CHBr3 proton? Enter your answer in the provided box. The odds against Carl beating his friend in a round of golf are 7:5. Find the probability that carl will beat his friend. What number fits the sequence, and why?What is the actual sequence? The porosity and permeability of a soil are influenced by the ____ of the soil.coloraciditystructurecopper contentfertility Is it possible to reject the notion of 'intrinsic value' as fuzzy and radically subject to individual opinion, and rely only on what has 'extrinsic value' since questions about what has what kind of consequences can be settled concretely? If two spheres have the same center but different radii, they are called concentric spheres.TrueFalse The variable z is directly proportional to x. When x is 6, z has the value 60. What is the value of z when x = 11? What university has the lowest acceptance rate? What term is used to describe how well an organism functions in itsenvironment? Consider the following system of equations:-1/3x^2 = -5/6 + 1/3y^2 and5y^2 = 25/2 - 5x^2How many solutions does the system have? A benign tumor differs from a malignant tumor. How does it differ? Abby has an exercise wheel with and 11 inches diameterFor her guinea pig. What is the circumference of the exercise wheel to the nearest whole number? Use 3.14 for The area rectangle,a=1xw is represented by the expression 24x6y15. Which could be the dimensions of the rectangle While waiting to pay for his weekly groceries at the supermarket, Paul had to wait about 20 minutes in a long line at the checkout because only one cashier was on duty. When he was finally ready to pay, his debit card was declined because he did not have enough money left in his checking account. Because he had left his credit cards at home, he had to place the groceries back into the cart and head home to retrieve a credit card. While driving back to his home, traffic was backed up two miles due to an accident. These events that Paul had to endure are best characterized as ________a. chronic stressorsb. acute stressorsc. daily hasslesd. readjustment occurrences what was germany's response not involving the military to the global depression What factors influence the rate of population growth of Eastern Europe What is the solution to this equation?X- 17 = -5